Pengaruh Model Project-Based Learning (PjBL) terhadap Kemampuan Berpikir Kritis Anak Usia 5-6 Tahun di TK Amal Kasih Ibu Sewar - Rindang Kiratna Hasanah; Ika Rachmayani; Filsa Era Sativa; Nurhasanah, Nurhasanah (Indonesian Publication Center, 2025)
Critical thinking is a crucial skill that should be developed from an early age to help children navigate daily life challenges. However, many Indonesian children still struggle to develop these skills optimally. This study addresses the deficiency in critical thinking among children at Amal Kasih Ibu Sewar Kindergarten. We aimed to determine the effect of a project-based learning model on the critical thinking skills of Group B children at this kindergarten. This research used a quantitative experimental method with a One Group Pretest-Posttest design. Sixteen Group B children participated in the study. Data were collected through observation and documentation and analyzed using normality (Shapiro-Wilk) and hypothesis (paired sample t-test) tests. Results showed a significant increase in critical thinking scores, from 46.47% (pretest) to 65.77% (posttest). The paired sample t-test confirmed a significant difference (p < 0.05; p = 0.000), indicating that the project-based learning model positively influenced critical thinking skills. Thus, project-based learning can be an effective solution for improving critical thinking skills in 5-6-year-old children at Amal Kasih Ibu Sewar Kindergarten.